Occupational health and safety of road haulage company employees - Riva, Matteo Marco; Cantamessa, Francesco; Borleri, Daniela; Mosconi, Giovanni (La Medicina del Lavoro, 2018)
Background: This paper follows up on a project that was launched in 2008 and contributed to the development of the new Italian Society of Occupational Medicine (SIML) guidelines for the road haulage industry. Objective: To reach a better understanding of occupational illness amongst truck drivers, in order to define appropriate health monitoring protocols and promote a healthy life-style. Methods: We assessed 673 male drivers (mean age 43.85 years, SD 9.56; mean working seniority 27.28 years, SD 10.59), employed by 46 different companies. The drivers, who were gradually recruited in the study over the years, had a maximum of 8 re-assessments each, for a total of 2608 examinations. We applied a survey protocol consisting in a medical examination, questionnaires for the most common risks and instrumental and laboratory tests in compliance with SIML guidelines. Results: We identified a total of 44 work-related diseases: 22 cases of noise-induced hearing loss (NIHL) and 22 cases of lumbar degenerative disc disease. As regards metabolic disorders, we observed 28 cases of diabetes mellitus, in most cases (71.4%) as a first diagnosis or under poor therapeutic control. We observed poorly-controlled hypertension in 103 drivers, the majority of whom (54%) were diagnosed for the first time. Over 30% of the workers in our study were obese and approximately 40% were tobacco smokers. We identified just 9 individuals (1.3%) with a positive toxicological screening for use of recreational drugs. Our data confirm a high prevalence of occupational illness amongst truck drivers. Cardiovascular and metabolic conditions require close monitoring.